Calcium Alginate and Salt/Phosphate as Binding Agents in Restructured Lamb - Setyawardani, Triana; Raharjo, Sri; sudarmadji, purnama (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2001)
A study on Â restructurization of lamb meat using several binding agents were conducted. Objectives of the study were evaluate Â effectivity of Caâalginate, salt and phosphate as binding agent and their effect on physical properties of the restructured meat stored at -20â°C for up to 12 weeks. Three binding agents were added to the restructured products, which include NaCl 0.3 %/ NTPP 0.3 %; alginate 0.5 %/Ca-lactate 0.5%; NaCl 0.3 % / NTPP 0.5 %/alginate 0.5% and no binding agent as a control. The products were evaluated at 0, 4, 8 and 12 weeks of storage. The result showed that treatment with alginate 0.5%/Ca-lactate 0.5% had the least purge loss value of 4.3Â±0.2%. The least cooking losses of 30.2Â±3.79% and the highest shear force 61.6Â±13.77 N. (Animal Production 3(1): 20-25 (2001)Key Words: Alginate/Ca-lactate, purge loss, cooking losses, shearÂ force.